2013
DOI: 10.1016/j.jceh.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Liver Disease: Bench to Bedside

Abstract: MicroRNAs (miRs) are small non-coding RNAs that negatively regulate gene expression by pairing with partially complementary target sequences in the 3 0 UTRs of mRNAs to promote degradation and/or block translation. Aberrant miR expression is associated with development of multiple diseases including hepatic diseases. The role of miRs in the regulation of gene expression and rapid progress in the field of microRNA research are resulting in momentum toward development of diagnostic markers and novel therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 159 publications
0
16
0
Order By: Relevance
“…On the other hand, although lots of technical challenges remain, many miRNAs represent promising targets for therapeutic gene therapy approaches . The studies discussed in the review suggest that targeting multiple miRNAs that regulate one target gene or multiple target genes controlling one particular process may provide an optimal therapeutic strategy.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, although lots of technical challenges remain, many miRNAs represent promising targets for therapeutic gene therapy approaches . The studies discussed in the review suggest that targeting multiple miRNAs that regulate one target gene or multiple target genes controlling one particular process may provide an optimal therapeutic strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have identified microRNAs, which are small, single‐stranded noncoding regulatory RNA molecules, as possible sensitive biomarkers for DILI . Notably, microRNA‐122 (miR‐122) is elevated earlier and demonstrates increased sensitivity in patients with acetaminophen‐induced liver injury compared with ALT .…”
mentioning
confidence: 99%
“…Circulating miRs are found in lipid or lipoprotein complexes providing an association between plasma miR levels and specifi c organ dysfunction [15]. miRs modulate diverse cellular processes associated with liver injury as infl ammation, apoptosis, and hepatocyte regeneration [16]. The miR-122 is liver specifi c and accounts for approximately 70% of all miRs in the liver [15].…”
Section: Micrornasmentioning
confidence: 99%